2016
DOI: 10.1038/srep34255
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular IL-33 cytokine, but not endogenous nuclear IL-33, regulates protein expression in endothelial cells

Abstract: IL-33 is a nuclear cytokine from the IL-1 family that plays important roles in health and disease. Extracellular IL-33 activates a growing number of target cells, including group 2 innate lymphoid cells, mast cells and regulatory T cells, but it remains unclear whether intracellular nuclear IL-33 has additional functions in the nucleus. Here, we used a global proteomic approach based on high-resolution mass spectrometry to compare the extracellular and intracellular roles of IL-33 in primary human endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 50 publications
(134 reference statements)
9
78
1
1
Order By: Relevance
“…Cells were maintained at confluence levels between 90%-100%, as confluency is critical for both LTR-IL-33 and native IL-33 expression [99, 107]. Cells were lysed and subjected to SDS-PAGE and western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were maintained at confluence levels between 90%-100%, as confluency is critical for both LTR-IL-33 and native IL-33 expression [99, 107]. Cells were lysed and subjected to SDS-PAGE and western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…IL‐33 has been shown to regulate chromatin compaction and NF‐κB transcriptional activity in transfected cells . However, when nuclear IL‐33 was knocked down in primary human endothelial cells, these cells displayed unaltered proteomes and NF‐kB expression as compared to that of the wildtype cells, suggesting that endogenous nuclear IL‐33 does not play a significant role in gene transcription . Furthermore, the mice lacking IL‐33 gene were fertile and did not appear to show gross abnormalities at the resting condition.…”
Section: Biological Functions Of Il‐33mentioning
confidence: 98%
“…Although they are less well characterized, non‐immune cells may also constitute important cellular targets of IL‐33 in vivo. These include endothelial cells, epithelial cells, fibroblasts, astrocytes, and neurons …”
Section: Activation Of St2‐expressing Cellsmentioning
confidence: 99%
“…However, after more than 10 years of research efforts, convincing evidence that endogenous nuclear IL‐33 regulates gene or protein expression is still lacking. Using a global proteomic approach, we recently showed that extracellular IL‐33 cytokine, and not endogenous nuclear IL‐33, regulates protein expression in primary human endothelial cells . High‐resolution mass spectrometry analyses revealed that knockdown of endogenous nuclear IL‐33 using two independent RNA silencing strategies had no reproducible effect on the endothelial cell proteome .…”
Section: Il‐33 a Nuclear Cytokinementioning
confidence: 99%
See 1 more Smart Citation